2017
DOI: 10.3329/pulse.v9i1.31874
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Nontuberculous Mycobacterium by Real Time PCR from Variety of Clinical Specimens

Abstract: Aim: Nontuberculous mycobacterium (NTM) causes many types of infections including respiratory and non-respiratory infections such as skin and soft tissue infections, lymphadenitis, meningitis, gastro-intestinal infections, disseminated infections and even intravenous catheter-related infections. Increasing incidence of NTM is reported worldwide in last decade. However, incidence of NTM in Bangladesh is not known as detection of NTM is not undergoing in Bangladesh which is necessary to know as these NTM species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Moreover, since all healthcare workers received BCG at birth, which is more than ten years prior to the TST, the result is less likely to be affected by the BCG exposures [ 56 ]. Thirdly, the study might have to overestimate TST positivity due to HCWs exposures to non-tuberculous mycobacteria, which are also prevalent in Bangladesh [ 11 , 57 ]. However, in a systematic review, Farhat et al (2006) showed that false-positive results due to non-tuberculous mycobacteria are not common in countries with high TB prevalence [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since all healthcare workers received BCG at birth, which is more than ten years prior to the TST, the result is less likely to be affected by the BCG exposures [ 56 ]. Thirdly, the study might have to overestimate TST positivity due to HCWs exposures to non-tuberculous mycobacteria, which are also prevalent in Bangladesh [ 11 , 57 ]. However, in a systematic review, Farhat et al (2006) showed that false-positive results due to non-tuberculous mycobacteria are not common in countries with high TB prevalence [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The discordance identified between TST and QFT-GIT might be attributable to several factors, including the effect of age on reactivity to TST, BCG vaccination status, and exposure to NTM, which are prevalent in Bangladesh [13,60]. We found a lower prevalence of TST PLOS ONE positivity among HCWs who started working at >30 years of age compared to other ages, while QFT-GIT positivity increased consistently with increasing age; this pattern is similar to results reported by other studies, where the decreased reaction to TST was attributed to the decreased ability of elderly skin to react [13,61].…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, since all healthcare workers received BCG at birth, which is more than ten years prior to the TST, the result is less likely to be affected by the BCG exposures [56]. Thirdly, the study might have to overestimate TST positivity due to HCWs exposures to non-tuberculous mycobacteria, which are also prevalent in Bangladesh [11,57]. However, in a systematic review, Farhat et al (2006) showed that false-positive results due to non-tuberculous mycobacteria are not common in countries with high TB prevalence [56].…”
Section: Plos Onementioning
confidence: 99%